Black women, separation allowances and citizenship in the French Caribbean during the First World War. (12th November 2020) - Joseph, Michael
Abstract: Historians of the First World War have shown great interest in the logics of gender and citizenship that governed the payment of separation allowances to soldiers' dependants and the ways in which these allowances structured subsequent European welfare regimes. Using the specific case of the French Caribbean, this article brings together two comparatively understudied dimensions of this history: the wartime legislation's implementation and the colonial context. It explores how discourses around race and labour, which had evolved in the context of emancipation and its aftermath, resonated with the assumptions encoded in the legislation. It then examines how Black Caribbean women mobilized to push back against the exclusions which followed. In so doing, it speaks to Black women's interventions in the political life of the Third Republic to resist their exclusion from the emerging French welfare state.